An integrated framework for modelling time-dependent corrosion propagation in offshore concrete structures. (1st February 2021) - Yu, Yuguo; Gao, Wei; Castel, Arnaud; Chen, Xiaojun; Liu, Airong
Highlights: The time-dependent corrosion propagation problem is numerically investigated. A novel framework is developed for effective predictions of corrosion propagation. Chemo-physical–mechanical and electrochemical modelling techniques are integrated. The proposed methodology is actively validated against a series of experiments. The continuous concrete decay has pivotal impact in long-term corrosion assessment. Abstract: Reinforcement corrosion is an enduring durability issue essential to the designs and maintenances of diverse offshore concrete structures. The corrosion propagation can be triggered and governed by a variety of environmental conditions, which is a complex process comprising the stages from time-dependent concrete decay during the initiation phase to the active corrosion phase. Misinterpretations and/or oversimplifications, due to difficulties in numerical modelling, on either phase would greatly impair the robustness of the estimation on corrosion rate. In this study, a novel numerical framework, integrating the chemo-physical–mechanical and electrochemical modelling techniques, is freshly developed to effectively address the conundrum in predicting time-dependent corrosion propagation. The developed framework is actively validated against a variety of experimental problems, where both long-term microcell and macrocell corrosions, as well as corrosions triggered under various sources are considered. The numerical studies thoroughly demonstrate the potential versatility of the proposed method in modern offshore civil engineering.